PENGARUH PESAN EDUKASI COVID-19 DI INSTAGRAM DR.TIRTA TERHADAP POLA HIDUP SEHAT DI MASA PANDEMI (Survei pada Pengikut Akun Instagram @dr.tirta) - Suhartanto, Muhammad Ramadhanu; M.A, Tsuroyya S.S (The Commercium, 2022)
This study aims to find out how much Dr. Tirta’s COVID-19 educational message on Instagram can affect the implementation of the lifestyle of followers of the @dr.tirta Instagram account during the pandemic. The method used is a survey method by distributing questionnaires to 430 followers of the Instagram account @dr.tirta. The results of this study prove that the COVID-19 educational message conveyed by Dr. Tirta on Instagram has a significant role of 0.16% in shaping the healthy lifestyle of his followers. This study also found that in the COVID-19 educational message variable, the education indicator for COVID-19 transmission found the highest value at 6.17. This indicates that Dr. Tirta has succeeded in influencing the trust of his followers in order to create a behavior that is more alert to the transmission of the COVID-19 virus. While on the healthy lifestyle variable, the indicator with the average value lies in the activity of doing sports with a value of 6.025. In this case, it can be said that followers of the Instagram account @dr.tirta responded to the COVID-19 educational message through the implementation of sports activities in order to improve the immune system and better metabolism during the pandemic. The application of this sport is in accordance with the goals and benefits during the pandemic where people can only stay at home and rarely do activities outside the home of the COVID19 virus. Keywords: Health messages, COVID-19 education, healthy lifestyle, Dr. Tirta.